TANTANGAN PROFESIONALISME DAN KESIAPAN GURU MENGIMPLEMENTASIKAN KURIKULUM 2013 - Budiwati, Neti; Sumartini, Sumartini; Pinayani, Ani (JURNAL EKONOMI PENDIDIKAN DAN KEWIRAUSAHAAN, 2016)
The purpose of this study was to obtain an overview of the level of competence, level of commitment and the level of creativity of high school Economics teachers in the context of the implementation of Curriculum 2013. The method used was a survey method. The study population was a teacher of economic subjects high school in Bandung, Bandung Regency, West Bandung and Cimahi with a total sample of 78 teachers. Data analysis was conducted by using a percentage (%), to describe the data and information to be achieved. The results showed that the level of competence of teachers Economics High School in Bandung Raya is still below the ideal score and only a small proportion are in the category of a high level of competence. The level of commitment from high school economics teacher in Bandung Raya is still below the ideal score and only a small percentage in the high category. Creativity level high school economics teacher in Bandung Raya is still below the ideal score and only a small proportion are in the category of highlevel creativity